IDENTIFICATION OF DERMATOPHYTES BY MULTIPLEX-POLYMERASE CHAIN REACTION, POLYMERASE CHAIN REACTION-RESTRICTION FRAGMENT LENGTH POLYMORPHISM ITS1-ITS4 PRIMERS AND MVAI, AND POLYMERASE CHAIN REACTION (GACA)4 PRIMER - Rizalinda Sjahril; Firdaus Hamid; Aan Yulianingsih; Novita Prastiwi; Awaluddin Awaluddin; Siska Nuryanti; Faridha Ilyas; Burhanuddin Bahar (UPT Penerbitan Universitas Jember, 2016)
Laboratory identification of skin lesion is important for the correct diagnosis and choice of therapy. Microscopic examination of skin or nail scraping or hair fragments in 10%-KOH provides rapid result but fungal growth in culture is required for identification of species. Unfortunately, culture requires a few days to 2 weeks, and there is variable colony appearance and colour. Rapid and correct diagnosis has been enabled by Polymerase Chain Reaction (PCR), but has not yet been applied for routine diagnosis of patients. Therefore we investigated the ability of culture using Saboraud Dextrose Agar, multiplex-PCR, PCR-RFLP with ITS1-ITS4 primers and MvaI, and PCR with (GACA)4 primer to identify of the etiology agents of 130 patients with tinea who were positive showing hyphae in 10%-KOH preparation. Skin scrapings were collected in Makassar during January-June 2016 and examinations were carried out in the Microbiology Laboratory of Hasanuddin University. Results: Dermatophytosis occurred in 73 (56,1%) males, and 57 (43,8%) females. Scraping was obtained from 78 (60%) skin and 52 (40%) nail lesions. Based on age stratification, 68 (52,3%) were 10-18 years old, 43 (33%) were 19-45 years old, and 19 (14,6%) were >45 years old. While 39 (30%) samples grew in culture, Multiplex-PCR, PCR-RFLP with ITS1-ITS4 primers and MvaI, and PCR with GACA4 primer amplified DNA of 130 (100%), 126 (96,9%), and 106 (81,5 %) samples, respectively. Multiplex-PCR was not able to distinguish between spesies in 99 (76,2%), PCR-RFLP with ITS1-ITS4 primers and MvaI in 29 (22,3%) and PCR with GACA4 primer in 20 (15,4%) samples.